PENGARUH CELEBRITY ENDORSEMENT DAN TESTIMONIAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPATU COMPASS DI MARKETPLACE INDONESIA - Eldon Hibatullah (2023)
In 2022 fashion products are in great demand by Indonesians when shopping online. The phenomenon that occurs is that Compass shoes are one of the best brands selling shoes in Indonesia at the moment. This research is a quantitative study with the aim of analyzing and proving the influence of Celebrity Endorsements and Testimonials on the Purchase Decision of Compass Shoes Products in the Indonesian Marketplace. This study uses a population of consumers who have made purchases at Compass Shoes in DKI Jakarta. The sample in this study used 100 respondents who were selected through nonprobability sampling and purposive sampling techniques. The data in this study were obtained from distributing questionnaires which would be analyzed using the Partial Least Square (PLS) method and assisted by using the SmartPLS application. The results obtained in this study were: (1) The Celebrity Endorsement variable had a positive and significant effect on the Purchase Decision variable with an Original Sample value of 0.542, (2) Testimonial Variables had a positive and significant effect on Purchase Decision variables with an Original Sample value of 0.425. Keywords: Celebrity Endorsement, Testimonials, Purchase Decision.